Are bladder cancer patients set at risk by minimally invasive approaches to radical cystectomy? - Niegisch, Günter (Translational Cancer Research; Vol 6, Supplement 1 (February 28, 2017): Translational Cancer Research, 2017)
Radical cystectomy is the mainstay of surgical treatment in muscle invasive bladder cancer (BC). With the advent of minimally invasive surgical approaches during the last decades an increasing number of patients has been treated by minimally invasive surgical approaches, namely conventional laparoscopic (LRC) and robotic assisted radical cystectomy (RARC). Despite comparable results to open radical cystectomy regarding perioperative outcomes, oncological surrogate parameters (margin status, lymph node yield) and early oncological outcomes these novel techniques are under debate. A controversial issue beyond cost effectiveness and short term clinical benefit is especially oncological safety. In this context a recent study on LRC report on early recurrences and unexpected patterns of metastases in bladder cancer patients with favourable tumor characteristics. This perspective article will detail and discuss the relevance of the findings of this controversial article regarding further advancement of minimally invasive approaches in radical cystectomy.